A 3D / 2D tin-lead perovskite solar cell based on tyramine hydrochloride and a preparation method thereof
By introducing tyramine hydrochloride into tin-lead perovskite solar cells, a 3D/2D heterostructure is formed, which solves the structural defect problem caused by Sn2+ oxidation, significantly improves the oxidation resistance and stability of the battery, and increases the energy conversion efficiency.
Patent Information
- Application Number
- CN202210155201.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-21
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-02-21
AI Technical Summary
Tin-containing perovskite solar cells face a strong chemical tendency to form Sn4+ by oxidation, resulting in structural defects, p-type doping and reverse saturation current, affecting the battery's energy conversion efficiency and stability.
Using the planar p-i-n structure of ITO/PTAA/tyramine hydrochloride-doped tin-lead perovskite/C60/BCP/Ag, tyramine hydrochloride is introduced through bulk doping and surface post-treatment to effectively passivate the film. defects and form 3D/2D heterostructures to improve antioxidant capacity.
Significantly improves the oxidation resistance and device stability of tin-lead perovskite solar cells, inhibits Sn2+ oxidation, and improves energy conversion efficiency and photostability.
Smart Images

Figure CN114551733B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tin-lead perovskite solar cells, and particularly relates to a 3D / 2D tin-lead perovskite solar cell based on tyramine hydrochloride and a preparation method thereof. Background Art
[0002] Organic-inorganic hybrid perovskite solar cells have attracted widespread attention from researchers due to their excellent energy conversion efficiency. Currently, the highest energy conversion efficiency of perovskite solar cells exceeds 25%, which is close to the efficiency of traditional inorganic silicon cells. At the same time, the advantages of perovskite cells such as low production cost and ease of large-scale production also pave the way for their future commercialization. Currently prepared high-efficiency perovskite solar cells mostly use lead-based components, but the high toxicity of heavy metal lead has always been a key problem that needs to be solved urgently. As an element of the same main group, perovskite solar cells prepared by replacing lead with tin have a series of unique advantages such as low toxicity and narrow band gap. However, the biggest challenge currently facing tin-containing perovskites is Sn 2+ Oxidation to form Sn 4+ This will destroy the integrity of the perovskite lattice, produce structural defects, lead to severe p-type doping and higher reverse saturation current. In addition, Sn 2+ Oxidation of tin-lead perovskite makes it easier to form defects when exposed to the atmosphere, heat or light, which seriously restricts the improvement of battery energy conversion efficiency and device stability. Therefore, finding a simple and effective method to inhibit the oxidation of tin-lead perovskite is of great significance for the development of efficient, stable and low-toxic perovskite photovoltaic devices. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a 3D / 2D tin-lead perovskite solar cell based on tyramine hydrochloride. The tin-lead perovskite solar cell prepared by the method has good oxidation resistance and device stability.
[0004] In the present invention, we use ITO / PTAA / tyramine hydrochloride doped tin-lead perovskite / C 60 / BCP / Ag planar pin structure is used to prepare perovskite solar cells. ITO is indium tin oxide, PTAA is polytriarylamine, C 60 It is a carbon 60 molecule, BCP is 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (bathocuproine), and Ag is silver.
[0005] The method for preparing a 3D / 2D tin-lead perovskite solar cell based on tyramine hydrochloride of the present invention comprises the following steps:
[0006] (1) Preparation of tin-lead-based perovskite precursor solution: Weigh 185.8 mg of formamidine iodide (FAI, Xi'an Biolight, 99.9%), 336.5 mg of lead iodide (PbI2, Xi'an Biolight, 99.99%), 149 mg of stannous iodide (SnI2, Alfa Aisa, 99.999%), 22.4 mg of methylamine bromide (MABr, Xi'an Biolight, 99.9%), 73.4 mg of lead bromide (PbBr2, Sigma-Aldrich, 99.99%), 6.3 mg of stannous fluoride (SnF2, J&K, 99.9%), and 4 mg of tin powder (Sn, J&K, 99.9%), and add 800 μL of N,N-dimethylformamide (DMF, J&K, ultra dry 99.9%) and 200 μL dimethyl sulfoxide (DMSO, J&K, ultra dry 99.9%) solvent were stirred in a glove box for 3 to 6 hours and filtered to obtain a clear tin-lead-based perovskite precursor solution;
[0007] (2) Preparation of PTAA hole transport layer solution: Weigh 1 mg of PTAA (polytriarylamine, Xi'an Baolait, 99.9%) solid and dissolve it in 1-2 mL of ultra-dry toluene (purified by distillation), and stir it in a glove box for 10-20 hours to obtain a PTAA hole transport layer solution;
[0008] (3) Preparation of tyramine hydrochloride-doped perovskite solution: Add tyramine hydrochloride (TACl, no crystal water, J&K, 99%) to the tin-lead perovskite precursor solution obtained in step (1), wherein the molar amount of tyramine hydrochloride is 0.1-0.7% of the molar amount of tin-lead perovskite in the precursor solution;
[0009] (4) Preparation of tyramine hydrochloride post-treatment solution: Weigh 0.1-5 mg of tyramine hydrochloride (TACl, no crystal water, J&K, 99%) solid and dissolve it in 0.5-1.5 mL of ultra-dry isopropanol (J&K, 99.9%), and stir in a glove box for 10-15 hours to obtain a tyramine hydrochloride solution with a concentration of 0.1-5 mg / mL;
[0010] (5) The PTAA hole transport layer solution prepared in step (2) is statically spin-coated on the surface of a clean glass / ITO (Hua Nan Xiangcheng, sheet resistance <15Ω / □, transmittance >85%) substrate at 4000-6000 rpm, and annealed on a hot plate at 90-110° C. for 8-15 minutes to complete the preparation of the PTAA hole transport layer, and the thickness of the PTAA hole transport layer is 5-10 nanometers; after cooling, the tyramine hydrochloride-doped perovskite solution prepared in step (3) is statically spin-coated on the surface of the PTAA hole transport layer at 4000-6000 rpm for 20-40 seconds, and 80-120 μL of ethyl acetate is dripped on the sample surface as an anti-solvent 10-20 seconds before the end of spin coating; and then annealed on a hot plate at 110-130° C. for 50-70 minutes to prepare a tyramine hydrochloride-doped tin-lead perovskite layer with a thickness of 400-500 nanometers;
[0011] (6) dynamically spin coating (i.e., the sample is spin-coated with the solution under high-speed rotation for dynamic spin coating; the sample is spin-coated with the solution under static state for static spin coating) 50 to 150 μL of the tyramine hydrochloride solution prepared in step (4) on the surface of the tyramine hydrochloride-doped tin-lead perovskite layer at 3000 to 5000 rpm; and then annealing on a hot plate at 90 to 110° C. for 5 to 10 minutes to form a small amount of 2D perovskite phase structure based on tyramine hydrochloride on the surface of the tyramine hydrochloride-doped tin-lead perovskite layer, while the bulk phase of the tyramine hydrochloride-doped tin-lead perovskite layer is a 3D perovskite phase structure, thereby forming a 3D / 2D tin-lead perovskite layer;
[0012] (7) At a vacuum degree of 4×10 -4 ~8×10 -4 Under the condition of Pa, the surface of the 3D / 2D Sn-Pb perovskite layer obtained in step (6) is sequentially evaporated with a thickness of 10 to 30 nanometers. 60 , a BCP with a thickness of 4 to 8 nanometers and a silver electrode with a thickness of 90 to 100 nanometers, thereby preparing the 3D / 2D tin-lead perovskite solar cell based on tyramine hydrochloride of the present invention.
[0013] In step (5), if the tin-lead-based perovskite precursor solution described in step (1) is directly used to prepare a pure tin-lead perovskite film by an anti-solvent method, there are often some structural defects at the internal grain boundaries and on the surface of the film, such as halogen vacancies, uncoordinated Pb 2+ Sn 2+ These structural defects act as non-radiative recombination centers for photogenerated carriers, causing carrier loss and affecting the device open circuit voltage and energy conversion efficiency. 2+ After contact with air, it is very easy to oxidize to form Sn 4+The present invention uses a new type of antioxidant tyramine (hydrochloride) as an organic cationic ligand, and introduces the antioxidant tyramine hydrochloride into the tin-lead perovskite film through two methods: bulk doping and surface post-treatment. The tyramine ligand can effectively bind to the uncoordinated Pb in the film. 2+ Sn 2+ The introduction of tyramine hydrochloride can effectively passivate the defects on the surface and inside of the perovskite film, and at the same time form a small amount of 2D layered perovskite phase on the surface of the 3D perovskite. This 3D / 2D heterostructure can effectively prevent water and oxygen from intruding, improve the antioxidant capacity of the film, and inhibit Sn 2+ Oxidation improves the storage stability of the device in the air.
[0014] At the same time, in the components of tin-lead perovskite, mixed halogens are usually introduced to adjust the band gap of the perovskite film. The movement of halogen ions in mixed halogen perovskites will lead to the generation of iodine-rich or bromine-rich phases, which is more obvious under light. Therefore, the solar cell often observes obvious phase separation problems caused by halogen segregation during operation, which brings difficulties to the final band gap adjustment and reduces the light stability of the device. After the present invention introduces tyramine hydrochloride, it will effectively passivate defects, fill halogen vacancies and inhibit the movement of halogen ions, thereby inhibiting halogen phase separation to a certain extent, improving the light stability of the perovskite film, and preparing an efficient and stable tin-lead perovskite solar cell.
[0015] In order to test the effectiveness of the introduction of tyramine hydrochloride to form a 3D / 2D structure in improving the photovoltaic performance of tin-lead perovskite solar cells, we modified the battery device by combining precursor doping (the technical solution after step 5, i.e., preparing a tin-lead perovskite layer using a tin-lead perovskite solution doped with tyramine hydrochloride to obtain a 3D structured tin-lead perovskite layer) with film post-treatment (the technical solution after step 6, i.e., preparing a tin-lead perovskite layer using a tin-lead perovskite solution doped with tyramine hydrochloride, and then post-treating the tin-lead perovskite layer with tyramine hydrochloride to obtain a 3D / 2D structured tin-lead perovskite layer) to prepare a typical planar pin structured perovskite solar cell and tested its current-voltage characteristic curve. The test results show that the device further post-treated with tyramine hydrochloride has further improved photovoltaic performance, especially stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 : The device structure diagram of the planar pin structure perovskite solar cell of the present invention, wherein from 1 to 6 are glass / ITO substrate 1, PTAA hole transport layer 2, 3D / 2D tin-lead based perovskite layer 3, C 60Layer 4, BCP layer 5 and silver electrode layer 6. The incident light is incident from the direction of the glass / ITO substrate 1.
[0017] Figure 2 :(a) High-resolution transmission electron microscopy image of pure tin-lead perovskite film;
[0018] Figure 2 : (b) High-resolution transmission electron microscopy image of tin-lead perovskite film post-treated with 0.5 mg / mL tyramine hydrochloride solution.
[0019] Analysis of the lattice fringes and spacing characteristics in the figure shows that there is only one area with uniform lattice fringes and fringe spacing in the pure tin-lead perovskite film. The corresponding phase is the 3D tin-lead perovskite phase. In contrast, two types of lattice fringes and spacings can be clearly observed in the perovskite sample treated with tyramine hydrochloride. The fringes and spacings are and These correspond to 3D and 2D perovskite phases, respectively. This indicates that a small amount of 2D perovskite phase is formed in the sample treated with tyramine hydrochloride.
[0020] Figure 3 :(a) The pure tin-lead perovskite film was placed in a nitrogen environment and illuminated by a 439 nm laser (5 mW / cm 2 ) X-ray diffraction peaks corresponding to the (110) and (220) crystal planes after irradiation of the sample for different time periods; (b) The tin-lead perovskite film treated with tyramine hydrochloride was placed in a nitrogen environment and irradiated with a 439 nm laser (5 mW / cm 2 ) After irradiating the sample for different time periods, the X-ray diffraction peaks corresponding to the (110) and (220) crystal planes were tested.
[0021] In Figure (a), curves 1, 2, 3, and 4 correspond to laser irradiation times of 0, 10, 20, and 40 minutes, respectively. It can be seen that as the irradiation time increases, the diffraction peak moves toward the direction of small angles, indicating that an iodine-rich phase is generated inside the film, indicating that phase separation caused by halogen segregation occurs in the film;
[0022] In Figure (b), curves 1, 2, 3, and 4 correspond to laser irradiation times of 0, 10, 20, and 40 minutes, respectively. It can be seen that after tyramine hydrochloride treatment, the diffraction peak has almost no obvious movement, indicating that the optimized film has improved light stability and suppressed halogen segregation.
[0023] Figure 4 : The current-voltage characteristic curve of the solar cell prepared by adding different molar percentages of tyramine hydrochloride to the tin-lead perovskite precursor solution as described in Example 1 of the present invention;
[0024] Curves 1, 2, 3, and 4 correspond to the current-voltage characteristic curves of devices with tyramine hydrochloride doping ratios of 0%, 0.1%, 0.3%, and 0.7%, respectively. As can be seen from the figure, the open circuit voltage and fill factor of the device doped with a small amount of 0.1% tyramine hydrochloride are significantly improved, and the energy conversion efficiency is improved. The optimal doping concentration is 0.3%. Further increasing the doping amount leads to a decrease in the short-circuit current of the device, which is due to the excessive introduction of insulating tyramine hydrochloride, which may affect the charge transfer properties.
[0025] Figure 5 : The current-voltage characteristic curve of the perovskite solar cell prepared by post-treating the perovskite with tyramine hydrochloride solutions of different concentrations as described in Example 2 of the present invention;
[0026] Curves 1, 2, 3, 4, and 5 in the figure correspond to tyramine hydrochloride post-treatment concentrations of 0, 0.1, 0.5, 1, and 5 mg / mL, respectively. As can be seen from the figure, the optimal post-treatment concentration is obtained at 0.5 mg / mL, and the device open circuit voltage, short circuit current, fill factor, and energy conversion efficiency are all improved, indicating its role in improving the photovoltaic performance of the device.
[0027] Figure 6 : Stability test curves of battery devices placed in air after packaging based on pure tin-lead perovskite, optimal tyramine hydrochloride precursor solution doped perovskite, and further using the optimal concentration of tyramine hydrochloride post-treatment perovskite;
[0028] Curves 1, 2, and 3 correspond to devices prepared by pure tin-lead perovskite solution, precursor solution doping, and precursor solution doping combined with thin film post-treatment, respectively. It can be seen that the device prepared by precursor solution doping combined with thin film post-treatment exhibits the best device stability, and its efficiency can still be maintained at about 80% of the initial efficiency after 1000 hours; followed by the device prepared by precursor solution doping, whose efficiency is about 71% of the initial efficiency after 300 hours. This difference in stability comes from the protective effect of the 2D perovskite formed on the surface against water and oxygen intrusion. DETAILED DESCRIPTION
[0029] Embodiment 1:
[0030] (1) Preparation of tin-lead-based perovskite precursor solution: Weigh 185.8 mg of formamidine iodide (FAI, Xi'an Biolight, 99.9%), 336.5 mg of lead iodide (PbI2, Xi'an Biolight, 99.99%), 149 mg of stannous iodide (SnI2, Alfa Aisa, 99.999%), 22.4 mg of methylamine bromide (MABr, Xi'an Biolight, 99.9%), 73.4 mg of lead bromide (PbBr2, Sigma-Aldrich, 99.99%), 6.3 mg of stannous fluoride (SnF2, J&K, 99.9%), and 4 mg of tin powder (Sn, J&K, 99.9%), and add 800 μL of N,N-dimethylformamide (DMF, J&K, ultra dry 99.9%) and 200 μL dimethyl sulfoxide (DMSO, J&K, ultra dry 99.9%) solvent were stirred in a glove box for 5 hours and filtered to obtain a clear tin-lead-based perovskite precursor solution;
[0031] (2) Preparation of PTAA hole transport layer solution: 1 mg of PTAA (Xi'an Biolight, 99.9%) solid was weighed and dissolved in 1 mL of ultra-dry toluene (purified by distillation), and stirred in a glove box for 15 hours to obtain a PTAA hole transport layer solution;
[0032] (3) Preparation of tyramine hydrochloride-doped perovskite solution: Tyramine hydrochloride (TACl, without crystal water, J&K, 99%) was added to the tin-lead perovskite precursor solution obtained in step (1), and the molar amount of tyramine hydrochloride was 0% (tin-lead perovskite precursor solution without tyramine hydrochloride doping), 0.1%, 0.3% and 0.7% of the molar amount of tin-lead perovskite in the precursor solution;
[0033] (4) Preparation of tyramine hydrochloride post-treatment solution: 0.5 mg of tyramine hydrochloride (TACl, no crystal water, J&K, 99%) solid was weighed and dissolved in 1 mL of ultra-dry isopropanol (J&K, 99.9%), and stirred in a glove box for 12 hours to obtain a tyramine hydrochloride solution with a concentration of 0.5 mg / mL;
[0034] (5) statically spin-coating the PTAA solution on the surface of a clean glass / ITO (Hua Nan Xiangcheng) substrate at 5000 rpm, and then annealing on a hot plate at 100° C. for 10 minutes to complete the preparation of the PTAA hole transport layer, the thickness of the PTAA hole transport layer being 5 nm;
[0035] (6) The ITO / PTAA surface obtained in the four steps (5) was statically spin-coated with a tin-lead perovskite solution having a molar amount of tyramine hydrochloride of 0%, 0.1%, 0.3%, and 0.7% of the molar amount of tin-lead perovskite in the precursor solution at 5000 rpm for 30 seconds, and 100 μL of ethyl acetate was dripped on the surface of the tin-lead perovskite solution as an anti-solvent 15 seconds before the end of the spin coating; then, the surface was placed on a hot plate for annealing at 120° C. for 60 minutes, and the thickness of the prepared tin-lead perovskite layer was 450 nm;
[0036] (7) At a vacuum degree of 6×10 -4 Under the condition of Pa, the surface of the tyramine hydrochloride-doped tin-lead perovskite layer obtained in step (6) is sequentially evaporated with a thickness of 20 nanometers of C 60 , 6-nm-thick BCP and 95-nm-thick silver electrode to prepare four tyramine hydrochloride-based 3D tin-lead perovskite solar cells.
[0037] Embodiment 2:
[0038] (1) Preparation of tin-lead-based perovskite precursor solution: Weigh 185.8 mg of formamidine iodide (FAI, Xi'an Biolight, 99.9%), 336.5 mg of lead iodide (PbI2, Xi'an Biolight, 99.99%), 149 mg of stannous iodide (SnI2, Alfa Aisa, 99.999%), 22.4 mg of methylamine bromide (MABr, Xi'an Biolight, 99.9%), 73.4 mg of lead bromide (PbBr2, Sigma-Aldrich, 99.99%), 6.3 mg of stannous fluoride (SnF2, J&K, 99.9%), and 4 mg of tin powder (Sn, J&K, 99.9%), and add 800 μL of N,N-dimethylformamide (DMF, J&K, ultra dry 99.9%) and 200 μL dimethyl sulfoxide (DMSO, J&K, ultra dry 99.9%) solvent were stirred in a glove box for 5 hours and filtered to obtain a clear tin-lead-based perovskite precursor solution;
[0039] (2) Preparation of PTAA hole transport layer solution: 1 mg of PTAA (Xi'an Biolight, 99.9%) solid was weighed and dissolved in 1 mL of ultra-dry toluene (purified by distillation), and stirred in a glove box for 15 hours to obtain a PTAA hole transport layer solution;
[0040] (3) Preparation of tyramine hydrochloride-doped perovskite solution: tyramine hydrochloride (TACl, no crystal water, J&K, 99%) was added to the tin-lead perovskite precursor solution obtained in step (1), and the molar amount of tyramine hydrochloride was 0.3% of the molar amount of tin-lead perovskite in the precursor solution;
[0041] (4) Preparation of tyramine hydrochloride post-treatment solution: 0.1, 0.5, 1, and 5 mg of tyramine hydrochloride (TACl, no crystal water, J&K, 99%) solid were weighed and dissolved in 1 mL of ultra-dry isopropanol (J&K, 99.9%), respectively, and stirred in a glove box for 15 hours to obtain tyramine hydrochloride post-treatment solutions with concentrations of 0.1, 0.5, 1, and 5 mg / mL, respectively;
[0042] (5) statically spin-coating the PTAA solution on the surface of a clean glass / ITO (Xiangcheng, South China) substrate at 5000 rpm, and annealing on a hot plate at 100° C. for 10 minutes to complete the preparation of the PTAA hole transport layer; the thickness of the PTAA hole transport layer is 5 nm;
[0043] (6) The ITO / PTAA surface obtained in step (5) was statically spin-coated with the tyramine hydrochloride-doped tin-lead perovskite solution obtained in step (3) at 5000 rpm for 30 seconds, and 100 μL of ethyl acetate was dripped on the surface as an anti-solvent 15 seconds before the end of the spin coating; then, the surface was placed on a hot plate for annealing at 120° C. for 60 minutes, and the thickness of the prepared tyramine hydrochloride-doped tin-lead perovskite layer was 450 nm;
[0044] (7) 100 μL of tyramine hydrochloride solution with concentrations of 0, 0.1, 0.5, 1, and 5 mg / mL, respectively, was dynamically spin-coated on the surfaces of five tyramine hydrochloride-doped tin-lead perovskite layers at 4000 rpm; the sample was then annealed on a hot plate at 100° C. for 10 minutes, so that a small amount of 2D perovskite phase structure based on tyramine hydrochloride was formed on the surface of the tyramine hydrochloride-doped tin-lead perovskite layer, while the bulk phase of the tyramine hydrochloride-doped tin-lead perovskite layer was a 3D perovskite phase structure, forming a 3D / 2D tin-lead perovskite layer;
[0045] (8) At a vacuum degree of 6×10 -4 Under the condition of Pa, the surface of the 3D / 2D Sn-Pb perovskite layer obtained in step (7) is sequentially evaporated with a thickness of 20 nm C 60 , a BCP with a thickness of 6 nanometers and a silver electrode with a thickness of 95 nanometers, thereby preparing 5 3D / 2D tin-lead perovskite solar cells based on tyramine hydrochloride according to the present invention.
Claims
1. A method for preparing a 3D / 2D tin-lead perovskite solar cell based on tyramine hydrochloride, the steps of which are as follows: (1) Preparation of tin-lead-based perovskite precursor solution: Weigh 185.8 mg of formamidine iodide, 336.5 mg of lead iodide, 149 mg of stannous iodide, 22.4 mg of methylamine bromide, 73.4 mg of lead bromide, 6.3 mg of stannous fluoride, and 4 mg of tin powder, add 800 μL of N,N-dimethylformamide and 200 μL of dimethyl sulfoxide solvent, stir in a glove box for 3 to 6 hours, and filter to obtain a clear tin-lead-based perovskite precursor solution; (2) Preparation of PTAA hole transport layer solution: Weigh 1 mg of PTAA solid and dissolve it in 1-2 mL of ultra-dry toluene. Stir in a glove box for 10-20 hours to obtain a PTAA hole transport layer solution; wherein, PTAA is polytriarylamine; (3) Preparation of tyramine hydrochloride-doped perovskite solution: adding tyramine hydrochloride to the tin-lead-based perovskite precursor solution obtained in step (1), wherein the molar amount of tyramine hydrochloride is 0.1-0.7% of the molar amount of tin-lead perovskite in the precursor solution; (4) Preparation of tyramine hydrochloride post-treatment solution: Weigh 0.1-5 mg of tyramine hydrochloride solid and dissolve it in 0.5-1.5 mL of ultra-dry isopropanol. Stir in a glove box for 10-15 hours to obtain a tyramine hydrochloride solution with a concentration of 0.1-5 mg / mL; (5) statically spin coating the PTAA hole transport layer solution prepared in step (2) on the surface of a clean glass / ITO substrate at 4000-6000 rpm, and annealing on a hot plate at 90-110° C. for 8-15 minutes to complete the preparation of the PTAA hole transport layer; After cooling, the tyramine hydrochloride-doped perovskite solution prepared in step (3) is statically spin-coated on the surface of the PTAA hole transport layer at 4000-6000 rpm for 20-40 seconds, and 80-120 μL of ethyl acetate is dripped onto the sample surface as an anti-solvent 10-20 seconds before the end of the spin coating; then, annealing is performed on a hot plate at 110-130° C. for 50-70 minutes to prepare a tyramine hydrochloride-doped tin-lead perovskite layer; (6) dynamically spin coating 50 to 150 μL of the tyramine hydrochloride solution prepared in step (4) on the surface of the tyramine hydrochloride-doped tin-lead perovskite layer at 3000 to 5000 rpm; then annealing on a hot plate at 90 to 110° C. for 5 to 10 minutes, so that a small amount of 2D perovskite phase structure based on tyramine hydrochloride is formed on the surface of the tyramine hydrochloride-doped tin-lead perovskite layer, while the bulk phase of the tyramine hydrochloride-doped tin-lead perovskite layer is a 3D perovskite phase structure, thereby forming a 3D / 2D tin-lead perovskite layer; (7) At a vacuum degree of 4×10 -4 ~8×10 -4 Pa, C 60 , BCP and silver electrodes to prepare 3D / 2D tin-lead perovskite solar cells based on tyramine hydrochloride; wherein BCP is 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline.
2. A 3D / 2D tin-lead perovskite solar cell based on tyramine hydrochloride, characterized in that: The method is prepared by the method of claim 1.
3. A 3D / 2D tin-lead perovskite solar cell based on tyramine hydrochloride as claimed in claim 2, characterized in that: The thickness of the PTAA hole transport layer is 5-10 nm, the thickness of the tyramine hydrochloride-doped tin-lead perovskite layer is 400-500 nm, and the C 60 The thickness of the electrode is 10~30 nanometers, the thickness of the BCP is 4~8 nanometers, and the thickness of the silver electrode is 90~100 nanometers.
Citation Information
Patent Citations
Modified perovskite type composite oxide, manufacturing method thereof, and composite dielectric material
CN102159498A
Optoelectronic devices and methods of making the same
US20200106019A1